Knowledge and Attitude on Learning Disabilities among Selected Primary School Teachers in Madi, Chitwan - Thapa, Asha; Dhakal, Bijaya; Lamichhane, Rama Kumari; Khatri, Anjana (International Journal of Silkroad Institute of Research and Training, 2024)
Backround: Learning disabilities (LD) represent a heterogeneous group of disorders manifested by significant difficulties in the acquisition and use of listening, speaking, reading, writing, reasoning, or mathematical abilities. Teachers play a pivotal role in identifying the child with LD and many aspects of treatment planning and implementation. This study aimed to find out the knowledge regarding learning disabilities among primary teachers of Madi Municipality, Chitwan. Methods: A descriptive cross-sectional study was carried out among 105 primary teachers from 10 government schools in Madi Municipality, Chitwan. A non-probability purposive sampling technique was used to select the sample. The data were analyzed in SPSS version 26, using descriptive statistics. Results: Among 105 respondents, 66.7 % were age group between 30-49 years. Regarding knowledge, 9.5%, 53.3%, and 37.2% of respondents had adequate, moderate, and inadequate level knowledge on learning disabilities respectively. Conclusion: Adequate knowledge on learning disabilities found to be low among respondents. The study highlights the necessity for targeted professional development programs for enhancing teachers' knowledge on learning disabilities, so that children can do well in school and have fulfilling lives in the future.